Efeito da terapia ativa não cirúrgica e da manutenção periodontal em indivíduos com câncer em região de cabeça e pescoço: um estudo prospectivo, controlado e pareado - Audrey Cristina Bueno (2013)
Studies that investigate the worsening of periodontal disease in patients undergoing radiotherapy for head and neck show increased periodontal attachment loss, which can be explained by a combination of factors such as the direct action of radiation on tissues, accumulation of bacterial biofilm and by altering the immune response of the host. However these studies are few and with small sample size. The purpose of this prospective study was to evaluate the onset of periodontal disease in patients undergoing radiotherapy with or without chemotherapy (test group) compared to patients not treated with radiotherapy (control group). The study was approved by the Ethics Committee of the Federal University of de Minas Gerais. A convenience sample was selected by continuous flow (n = 56). The test and control groups (n=28) were homogenized with respect to gender, age, smoking, alcoholism and periodontal clinical diagnosis. A baseline measurement (T0) of clinical periodontal parameters: bleeding on probing (BOP), probing depth (PD), clinical attachment level (CAL) and gingival recession (GR), and plaque index (PI), performed on all teeth, and was made before the start of cancer treatment. Periodontal treatment was performed according to the needs of the patient. The periodontal evaluations were conducted until 15 days after the end of radiotherapy (T1), 180 days (T2) and 1 year (T3) for the test group. For the control group, periodontal evaluations were performed 3 months after the initial assessment, followed by two more assessments with an interval of 6 months between them. Descriptive measures of periodontal parameters were reported in absolute frequency and relative means and percentages when appropriate. For each patient, the means of PS, NI and RG were obtained by dividing the sum of clinical periodontal by the number of sites examined. These values were compared over time for each group using the Friedman test; and the Mann-Whitney test was used for comparisons between groups. The results were considered significant for a probability of less than 5% significance (p <0.05). There was significant reduction of plaque index between T0 and T2 and between T0 and T3 in the test group. Significant reduction of plaque index between T0 and the others moments of evaluation (T1, T2 e T3) in the control group. For both groups, there were significant reduction in probing depth between the baseline evaluations and six month. There are differences between the groups with respect to bleeding on probing in the evaluation T0, T1 e T2, and gingival recession at all time points. The probing depth evaluation the differences were just in six months and one year evaluation. Patients in the test and control groups showed no worsening condition probably due to periodontal treatment and periodontal maintenance received during follow-up, but a greater increase of gingival recession in the test group may suggest a direct action of radiation on the periodontal tissues.